(3QSGdI aj GdYQhVs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s
(3ChdgG (B:s
(3addLRA MJekG hHd ef aEf JQO LhGRkG aLgQ hdcf EPG eG Md HjJkG aEfg jchf HHGbi GdfXe MJekG HdG s
(3BNQgG (B:s
(3ef afi GdYQhV hGdbGajI jUjQ eG gQkG ai eYQaI GdCTYGQ GdYQHjI hGdCHjGJ GdaGQSjI hGddg JYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs